Regional Government and Regional Planning in the Hanover Region - Priebs, Axel (Quaestiones Geographicae, 2014)
The Hanover Region was created in 2001 as a new type of urban regional body. The article deals with the conditions and goals of this administrative reform. It examines factors that contributed to the success of the reform. It is emphasised that above all the region’s predecessors’ more than three decades of experience with regional tasks were crucial. Also important was the fact that the region was initiated by three ‘doers’ from the local level, starting a bottom-up process. Crucial for the region’s profile is solidarity between the municipalities with their different economic and social structures. This is guaranteed by the contribution that all municipalities pay to the region. The article also deals with the regional planning principles in the Hanover Region, which has attempted to prepare and maintain a comprehensive physical structure. It is pointed out that the main advantage of the Hanover Region is that there is political responsibility at the regional level with directly elected politicians